Wyznaczniki gatunkowe recenzji w "Monitorze" = Genre criteria of reviews in "Monitor" - Gorzelana, Joanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the article is to present the genre features of reviews in terms of structural, cognitive, stylistic and pragmatic approach. The analysed text was formally a letter to the editor of the "Monitor" magazine, published in No. 20 of 1783. This text refers to the satire entitled "A gift for Warsaw ladies, or a Fashionable Parishioner from Cracow`s piedmont".
Keywords: oświecenie; "Monitor" - czasopismo; gatunek; recenzje; satyra; dama; Enlightenment; "Monitor" magazine; genre; review; satire; lady